Influence of Intellectual-cultural Orientation as Family Culture on Chinese College Students' Subjective Well-being: A Moderation Model - Guangming Li PhD; Yuelin Wu BS; Haiying Wen MS; Fadi Zhang HS; Desheng Yan PhD (SAGE Publishing, 2022)
The well-known mediation-moderation model of subjective well-being has been criticized because it oversimplified the concept of culture. This study aimed to explore whether the family culture, as supplement of social culture, has significant impacts on subjective well-being. The intellectual-cultural orientation subscale (ICO) of family environment scale-CV (FES-CV), Eysenck personality questionnaire for adult (EPQA), and index of well-being (IWB) were used to test 340 college students from China. Results showed that the extraversion and neuroticism of personality traits have great influences on subjective well-being, and intellectual-cultural orientation as family culture, to represent characteristic of family culture, serves as a moderating variable for the 2 components of subjective well-being. And all these findings revealed that the trait of family culture should be considered as a supplement of the social culture and a critical complementary moderating influenced factor for subjective well-being. Together with personality traits, it can explain the variance of subjective well-being to some extent. The family cultural has an important influence on college students' personality and subjective well-being. It is important to provide a high quality family cultural environment for college students.